Effects of Dentifrice Containing Hydroxyapatite on Dentinal Tubule Occlusion and Aqueous Hexavalent Chromium Cations Sorption: A Preliminary Study - Yuan, Peiyan; Shen, Xiaoqing; Liu, Jing; Hou, Yarong; Zhu, Manqun; Huang, Jiansheng; Xu, Pingping (PLOS ONE, 2012)
In order to endow environmental protection features to dentifrice, hydroxyapatite (HA) was added to ordinary dentifrice. The effects on dentinal tubule occlusion and surface mineralization were compared after brushing dentine discs with dentifrice with or without HA. The two types of dentifrice were then added to 100 µg/ml of hexavalent chromium cation (Cr6+) solution in order to evaluate their capacities of adsorbing Cr6+ from water. Our results showed that the dentifrice containing HA was significantly better than the ordinary dentifrice in occluding the dentinal tubules with a plugging rate greater than 90%. Moreover, the effect of the HA dentifrice was persistent and energy-dispersive spectrometer (EDS) revealed that the atomic percentages of calcium and phosphorus on the surface of dentine discs increased significantly. Adding HA to ordinary dentifrice significantly enhanced the ability of dentifrice to adsorb Cr6+ from water with the removal rate up to 52.36%. In addition, the sorption was stable. Our study suggests that HA can be added to ordinary dentifrice to obtain dentifrice that has both relieving dentin hypersensitivity benefits and also helps to control environmental pollution.